Community‑Based Mentoring on Kitab Kuning Literacy through the Integration of Sorogan, Bandongan, and Multimedia to Strengthen Fiqh and Moral Education for Adolescents - Muhamad Fathoni Fathoni; Cahya Edi Setyawan; Yumna Yumna (Transformatif: Jurnal Pengabdian Masyarakat, 2026)
This community service program aimed to improve kitab kuning literacy, particularly in reading accuracy, glossing skills, and comprehension of fiqh and moral education materials, while also strengthening learning motivation and character development among adolescents in Genting, Tirtomulyo, Kretek, Bantul. The program used a qualitative community‑based educational mentoring design and was conducted for one month with 17 adolescents. The implementation followed four stages: initial ability mapping, projector‑assisted bandongan for collective modeling, individual sorogan for reading verification, and group and individual mentoring for remediation. Data were collected through interviews, observation, and documentation. The results show that projector‑assisted bandongan accelerated contextual understanding, while sorogan improved reading discipline and accuracy. Individual mentoring helped reduce gaps in vocabulary, grammar, and diacritics. Moral values from the texts became more meaningful when connected to adolescents' daily lives. Overall, the program improved kitab kuning literacy, motivation to learn Arabic, and character development. Its novelty lies in combining traditional pesantren methods (bandongan and sorogan) with multimedia support while maintaining both as the core learning methods.